Densities in the quiet sun and coronal holes using EUV emission lines - Dwivedi B.N. (My University, 2025)
The density dependence of solar EUV line intensity ratios from Mg VIII, Si VII, S IX and Si IX ions have been used to determine electron densities in the quiet Sun and coronal holes. The line intensity values have been computed using a model atmosphere of Kopp and Orrall (1976) in order to emphasize the utility of the lines studied which could be compared with observational data that future missions might provide. © 1989 Kluwer Academic Publishers.